Cloud service negotiation: a research report. (1st January 2014) - Zheng, Xianrong; Martin, Patrick; Brohman, Kathryn; Zhang, Mingyi
As the cloud market becomes more open and competitive, Quality of Service (QoS) will be more important. To allow cloud consumers to express their QoS requirements, and negotiate them with cloud providers, we argue for cloud service negotiation. This paper outlines a research roadmap, reviews the state of the art and reports our work on cloud service negotiation. Three research problems that we formulate are QoS measurement, QoS negotiation and QoS assurance. To address QoS measurement, we initiate a quality model for cloud services, called CLOUDQUAL, which specifies six quality dimensions and five quality metrics. To address QoS negotiation, we present a mixed negotiation approach for cloud services, which is based on the 'game of chicken' and can balance utility and success rate. To address QoS assurance, we propose a QoS-driven resource allocation method for cloud services, which can meet users' QoS requirements while minimising resources consumed.